2013
DOI: 10.1093/mnras/stt757
|View full text |Cite
|
Sign up to set email alerts
|

Studying the relationship between X-ray emission and accretion in AGN using the XMM–Newton Bright Serendipitous Survey

Abstract: We study the link between the X-ray emission in radio-quiet active galactic nuclei (AGN) and the accretion rate on the central supermassive black hole using a statistically well-defined and representative sample of 71 type 1 AGN extracted from the XMM-Newton Bright Serendipitous Survey. We search and quantify the statistical correlations between some fundamental parameters that characterize the X-ray emission, i.e. the X-ray spectral slope, , and the X-ray 'loudness', and the accretion rate, both absolute ( Ṁ)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 42 publications
10
60
0
Order By: Relevance
“…This equals 6%-13% of the bolometric luminosity estimated by Moorwood et al (1996) from mid-IR spectroscopy, where most of the nuclear mid-IR flux is identified with reprocessed AGN emission. This L 2−10 /L bol ratio is within the range of X-ray to bolometric luminosity ratios found in type 1 AGN (e.g., Elvis et al 1986;Fanali et al 2013). Gandhi et al (2009) calculate the L 2−10 keV /L 12 μm using nuclear IR luminosities, as opposed to the large aperture ISO values quoted above, finding an almost linear relation with 0 intercept.…”
Section: Discussionsupporting
confidence: 80%
“…This equals 6%-13% of the bolometric luminosity estimated by Moorwood et al (1996) from mid-IR spectroscopy, where most of the nuclear mid-IR flux is identified with reprocessed AGN emission. This L 2−10 /L bol ratio is within the range of X-ray to bolometric luminosity ratios found in type 1 AGN (e.g., Elvis et al 1986;Fanali et al 2013). Gandhi et al (2009) calculate the L 2−10 keV /L 12 μm using nuclear IR luminosities, as opposed to the large aperture ISO values quoted above, finding an almost linear relation with 0 intercept.…”
Section: Discussionsupporting
confidence: 80%
“…Higher L Bol /L Edd is expected to lead to increased Compton cooling of the accretion-disk corona, and thus steeper 2-10 keV power-law spectra (i.e., larger values of Γ ; higher L Bol /L Edd also often leads to the production of a strong "soft X-ray excess" affecting the spectrum below rest-frame 2 keV). The early suspicions have now been confirmed via both targeted (e.g., Shemmer et al 2006Shemmer et al , 2008 and X-ray survey-based (e.g., Risaliti et al 2009;Jin et al 2012a;Brightman et al 2013;Fanali et al 2013) studies, which find clear Γ − L Bol /L Edd correlations across a broad range of luminosity and redshift (and no apparent redshift dependence); see Fig. 10.…”
Section: X-ray Continuum Shape As An Estimator Of Eddington Ratiomentioning
confidence: 85%
“…If we adopt, for example, the luminosity-dependent bolometric correction of Marconi et al (2004), we would obtain L6 µm ∝ L 0.750±0.024 bol for the full sample of objects (for a similar luminositydependence of the hard X-ray bolometric correction see also Hopkins, Richards, & Hernquist 2007). More recent studies in the literature suggest, however, a much weaker dependence of the hard X-ray bolometric correction with AGN luminosity if any (Vasudevan & Fabian 2007;Marchese et al 2012;Fanali et al 2013).…”
Section: --mentioning
confidence: 91%